The divine personhood of the Holy Spirit in the teaching of Gregory Nazianzen - Artemi, Eirini (Vox Patrum, 2018)
Gregory of Nazianzus had to confront with courage the heretical teaching about the divine nature of Holy Spirit. Through his works, he identifies The Holy Spirit as the third Person of the Triune God. One can see that the Bible clearly teaches that the Spirit is God. The Holy Spirit just as the Son, originates from the Father, is coeternal with the Father and illuminates the whole creation. The third Person of Trinity deserves to be worshipped as God and deifies people in their baptism. Gregory wonders: “For if He is not to be worshipped, how can He deify me by Baptism? But if He is to be worshipped, surely He is an Object of adoration, and if an Object of adoration He must be God; the one is linked to the other, a truly golden and saving chain. And indeed from the Spirit comes our New Birth, and from the New Birth our new creation, and from the new creation our deeper knowledge of the dignity of Him from Whom it is derived” (Oratio 31, 28). Gregory underlined the divinity of Holy Spirit and also explained the soteriological goal of this teaching, because: “If he has the same rank as I have, how can he make me God, or how can he join me with deity” (Oratio 31, 4).